Analysis and Design of a Dual-polarized Printed Monopole Antenna. Issue 6 (2nd November 2021) - Song, Lizhong; Geng, Jinling
ABSTRACT: In this paper, we present the design, fabrication, and measurement results of a dual-polarized printed monopole antenna with the low-return loss. The dual polarization is provided by printing two orthogonal monopoles on FR4 substrate. To improve the port matching and the isolation between two ports, we design and print a feed ground with a chamber corresponding to each printed F-type feed-line. The proposed antenna achieves a 10 dB return loss bandwidth of 1.081–1.158 GHz at both two ports and isolation better than 20 dB in the whole band. Based on the conventional printed-circuit board technology, the proposed antenna has a lightweight and low-cost construction. There is a good agreement between the measured and the simulated results.